2014
DOI: 10.4102/jsava.v85i1.1047
|View full text |Cite
|
Sign up to set email alerts
|

The effects of midazolam and butorphanol, administered alone or combined, on the dose and quality of anaesthetic induction with alfaxalone in goats

Abstract: Goats are rarely anaesthetised; consequently, scant information is available on the efficacy of anaesthetic drugs in this species. Alfaxalone is a relatively new anaesthetic agent, of which the efficacy in goats has not yet been studied. In this study, the sedative and alfaxalone sparing effects of midazolam and butorphanol, administered alone or concomitantly, in goats were assessed. Eight clinically healthy goats, four does and four wethers, were enlisted in a randomised crossover manner to receive intramusc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 34 publications
(70 reference statements)
3
28
2
Order By: Relevance
“…Compared with the reported dose of 3 mg kg −1 when alfaxalone is used alone for induction (Dzikiti et al. ), fentanyl markedly reduces the alfaxalone dose for induction of anaesthesia, even at the lowest fentanyl dose 0.005 mg kg −1 used in the present study. This observation is in agreement with what has been previously reported for other inductions agents in various species such as propofol in humans (Bansal et al.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations
“…Compared with the reported dose of 3 mg kg −1 when alfaxalone is used alone for induction (Dzikiti et al. ), fentanyl markedly reduces the alfaxalone dose for induction of anaesthesia, even at the lowest fentanyl dose 0.005 mg kg −1 used in the present study. This observation is in agreement with what has been previously reported for other inductions agents in various species such as propofol in humans (Bansal et al.…”
Section: Discussioncontrasting
confidence: 71%
“…As already stated earlier, premedication with drugs such as midazolam might ameliorate the excitatory effects associated with fentanyl in goats (Dzikiti et al. , ).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Midazolam has been shown to act synergistically with other induction agents [20] and is reported to reduce the induction dose of propofol in both dogs and cats [21,22]. Reduced respiratory rates associated with midazolam have been previously reported in horses and rabbits [8,25] along with increased post-induction apnoea in horses and goats [26,27], although these are not consistent observations [26,28]. Nishimura et al [23] demonstrated that midazolam has no intrinsic analgesic properties but when co-administered with dexmedetomidine it enhanced analgesia in rats [24].…”
Section: Discussionmentioning
confidence: 98%